Effect of Negative Pressure Therapy on Open Abdomen Treatments. Prospective Randomized Study With Two Commercial Negative Pressure Systems - Auer, Thomas; Sauseng, Siegfried; Delcev, Pavle; Kohek, Peter (Frontiers in Surgery, 2021)
Introduction: The use of negative pressure dressings for open abdominal therapy has made a great impact on strategies for open abdominal treatment. Observed intestinal damage and developement of fistula formation raises questions about safety of comonly used systems (AB-Thera). The most common used system uses foils for shielding intestines directly from negative pressure. As an alternative a system with open pore dressing in double layer film was introduced (Suprasorb CNP) and proved to safe in animal studies. We compared the effects of this two systems on patients requiring open abdominal treatment. Materials and methods: Patients with secondary peritonitis in at least two abdominal quadrants were included in this randomised study. Inclusion criteria were secondary peritonitis (ACS), abdominal compartment syndrome and abdominal trauma combined with ACS and/or contaminated abdomen. Patients with active bleeding and pancreatitis were not included. We examined Mannheim peritonitis Index (MPI), bloodcount, PCT, amount of fluid collected and morphological changes on the bowel. Data were collected on day 2, 4, 7, 14. 21, 28. Primary end point was fascial closure. Examination was terminated in case of death and damage to the abdominal organs. Groups were compared using Mann Whitney U test and chi square test. Trend evaluation was evaluated using an one way repeated measure analysis of variance. P values below 0.05 was considered significat. Results: Thirty four patients were included between August 2010 and September 2012. There were no significant difference between two groups in MPI, age and gender. Mean duration of treatment, WBC, CRP and abdominal closure rate were not significantly different between groups. Suprasorb CNP System collected twice more fluid than AB-Thera and decreased PCT on significantly faster rate than AB-Thera. Four patients died (11%) and four patients developed enteric fistula (11%). Closure rate was achieved in 27 out of 34 Patients (79.5%). Closure rate was not significantly different between groups. Conclusion: The use of both systems proved to be efficient and safe. The application of well-dosed, moderate negative pressure on contaminated areas of the abdomen seems to have a lot of potential and it is worth directing greater research potential in this direction